DEVELOPMENT OF THE GENERALIZED SIMULATION MODEL OF A MOBILE COMMUNICATION SYSTEM ON THE BASIS OF AGGREGATE APPROACH - Kichak, Vasiliy; Vasilskaya, Maya (Scientific Works of Vinnytsia National Technical University, 2015)
Elaboration of a generalized, open for modifications working mathematical model of the multichannel queue system with arbitrary servicing disciplines is proposed and substantiated. Functional subsystems of the imitation model are built as aggragates. The model is designed for simulation of the processes in mobile communication systems.